Strategic Planning with Comprehensive Budgeting to Optimize Management Control in the MSME Sector Post-Pandemic: A Literature Review - Mediaty, Mediaty; Usman, Asri; Paembonan, Aunneke Julisda; Ilham, Zuhalwah Yuliah; Namra, Namra (UNIVERSITAS PAKUAN, 2025)
This study aims to analyze the application of strategic planning with a comprehensive budgeting approach in optimizing management control in Micro, Small, and Medium Enterprises (MSMEs) during the post-pandemic recovery period. By synthesizing various recent studies, this study identifies the main factors that influence the effectiveness of integrated budgeting as well as the challenges faced by MSMEs in aligning strategies and control mechanisms. This study uses the Systematic Literature Review (SLR) method with data sources obtained through Publish or Perish, Science Direct, IEEE, Scopus, Taylor and Francis, Google Scholar, and ProQuest, resulting in 40 reputable journals published in 2021–2025 that are relevant to the research topic. The findings show that strategic planning and comprehensive budgeting play an important role in improving decision-making, accountability, and the managerial performance of MSMEs. However, its success is greatly influenced by leadership commitment, managerial competence, digital readiness, and government policy support. The main challenges faced by MSMEs include financial constraints, low managerial literacy, and inadequate technological infrastructure, which hinder the integration of planning, budgeting, and control. This study implies the need for government support through policies and programs to increase the capacity of MSMEs to strengthen strategic financial management. For MSME actors, the integration of strategic planning and comprehensive budgeting can be a means to achieve efficiency, resilience, and sustainable business growth in the post-pandemic era. This study offers a new perspective on the relationship between strategic planning, comprehensive budgeting, and management control in the MSME sector, highlighting their synergy as drivers of organizational recovery and sustainability.